Biosurfactant enhanced biodegradation of high molecular weight polycyclic aromatic hydrocarbons in a two-stage continuous stirred tank bioreactors and biofilm tank - Chirwa, Evans M.N. (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2017.